possible relationship between school performance and motor skills: a neural network approach. DOI: 10.5007/1980-0037.2011v13n5p373 - Andrzej Tukiendorf; Maria Fátima Glaner; Cezary Kuśnierz; Jan Szczegielniak (Universidade Federal de Santa Catarina, 2011)
The aim of this study was to answer the question whether a relationship exists between school grades reflecting humanistic, synthesis, ecological, and physical skills and motor skills (speed and power) in middle school adolescents. The following tests were used for the evaluation of the particular motor skills: plate tapping test for the measurement of upper limb speed, Fleishman test for the measurement of lower limb speed, medicine ball throwing for the evaluation of upper limb power, and standing broad jump for lower limb power testing. The data were analyzed using a neural network approach. The results indicated that the school grades of middle school adolescents can be used to predict motor power. In this case, the linear correlation coefficient (r) between the actual and predicted data exceeded the level of r = 0.9. In particular, a strong statistical impact of ecological, synthesis and physical skills on power performance was established. In contrast, a weaker correlation was observed with motor speed performance (r < 0.6). More attention should be paid to the possible relationship between school grades and motor skills in children and adolescents. This information is important, particularly for the selection of youngsters with advanced motor skills at an early age.